Effect of extractives on wood density and natural durability of tristaniopsis whiteana and T.beccaril (myrtaceae) - Farawahida, Abu Zaharin (Universiti Malaysia Sarawak (UNIMAS), 2013)
Extractives are organic compound contained in wood parenchyma cell, cell lumina, and intercellular cavities which can be removed by organic solvents. Density and durability are two important wood quality indicators that are known to be influenced by extractives content. However, the influence of extractives content on wood density and durability are less documented for tropical hardwood species. The aim of this study was to determine the effect of extractives content on wood density and durability of Tristaniopsis whiteana and T. beccarii. The specific objectives of this study were to (i) determine the effect of extractives on wood density, (ii) determine decay resistant of T. whiteana and T. beccarii and (iii) to characterize chemical compounds in the extractives obtained from T. whiteana and T. beccarii. The samples were obtained from three height levels and across the radial of each level. Wood blocks were subjected to sequential extraction first by using hexane, followed by dichloromethane, ethyl acetate, methanol and finally distilled water. The density of unextracted and extracted wood blocks were determined prior to decay test. Extractives were extracted using hexane, DCM, ethyl acetate and methanol, and subjected to Gas Chromatography - Mass Spectrometry (GC-MS) analyses. Results showed that densities of wood blocks significantly reduced following of solvents extraction. Relationship between airdry densities and extractives content for both species studied were positive with coefficient of determination (r2) ranged from 0.52 to 0.58. Natural durability test showed that T. whiteana and T. beccarii were classified as durable. However following extraction, the wood became non-durable to Trametes versicolor, Pycnoporus sanguineus and Chaetomium globosum.Relationship between total extractives content and weight loss due to decay were inversed which indicates the higher the extractives content the lesser the decay activity. The main compounds detected by GC-MS for T. whiteana extracts were tetradecylcyclooctane, heptadecylcyclohexane, eicosane, tetracontane, 1,2-benzenedicarboxylic acid, 1-nonadecene, β-sitosterol, malonic acid and betulin. Meanwhile, major compounds in T. beccarii were Cis, Cis trans-1-Isobutyl-2,5-dimethylcyclohexane, pentadecylcyclohexane, 1,2- benzenedicarboxylic acid, 1-nonadecene, β-sitosterol, γ-sitosterol and malonic acid.